PERANCANGAN SISTEM INFORMASI PERSEDIAAN BARANG PADA PT BINA SAN PRIMA KARAWANG - dede firmansyah saefudin; Yuli Komalasari (Universitas Islam Kuantan Singingi, 2020)
Merchandise inventory is very important for trading companies and manufacturing companies. Inventory is needed to create sales for a profit. Inventories are current assets that have a high enough risk in company activities if they are not considered properly. The inventory process at PT. Bina San Prima can be said to be still inefficient and ineffective because everything is still done manually, starting from the process of recording goods data, processing incoming goods data and outgoing goods data, processing goods data reports. This access does not yet have a good inventory information system, also for ordering data from suppliers there is no minimum stock data specified so that orders can be made to the supplier so that sometimes the stock is out of stock and then ordered to the supplier, and it hampers the goods if there is a purchase from the customer. The program application is an alternative solution to the problems faced by companies or agencies, especially PT. Bina San Prima, in this case, especially in making inventory reports. With this programming application, filling and storing data will be easier and safer.